Pandemic of the century: COVID-19 in inflammatory rheumatic diseases of a national cohort with 3,532 patients - Selda Sarıkaya; Şebnem Ataman; Erhan Eser; Özgür Akgül; Ata Bora Ayna; Nesrin Şen; Rengin Güzel; Meltem Alkan Melikoğlu; Mustafa Erkut Önder; Erhan Çapkın; et al. (Archives of Rheumatology, 2024)
Objectives: This study aimed to assess the clinical outcomes and risk factors for severe coronavirus disease 2019 (COVID-19) in patients with inflammatory rheumatic disease (IRD) of a national cohort. Patients and methods: The multicenter cross-sectional study was carried out between July 15, 2020, and February 28, 2021. Data collection was provided from a national network database system, and 3,532 IRD patients (2,359 males, 1,173 females; mean age: 48.7±13.9 years; range; 18 to 90 years) were analyzed. Demographics, clinics about rheumatic disease, comorbidities, smoking status, being infected with COVID-19, and the course of the infection were questioned by rheumatology specialists. Results: One hundred seventeen patients were infected with COVID-19, the hospitalization rate due to COVID-19 was 58.9%, and the mortality rate was 1.7%. There was no difference between the COVID-19 positive and negative groups in terms of rheumatic disease activities and receiving drugs. It was observed that patients with COVID-19 had worse compliance with isolation rules, and bacillus Calmette-Guérin (BCG) vaccination was less common. The mean age and the rate of smoking of hospitalized COVID-19 patients were higher than those without hospitalization. Conclusion: In this cohort, in which real-life data were analyzed, COVID-19 rates in IRD patients were similar to the general population for the same period. Compliance with the isolation rules and BCG vaccination attracted attention as components that reduce the risk of COVID-19 infection. The risk factors for hospitalization were older age and smoking.